EVALUASI FAKTOR-FAKTOR SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PROYEK REHAB RUMDIS 2 LANTAI HUBDAM XVI/PATTIMURA-AMBON - Lekatompessy, Marchel; Leuhery, Lenora; Istia, Penina (Journal Agregate, 2024)
The Hubdam XVI/Pattimura-Ambon 2-Storey Rumdis Rehab Project is one of the construction projects that has a high risk of work accidents because workers who do not comply with regulations to wear PPE are also because they are close to other official housing and close to road access commonly used by the surrounding community. This study aims to determine what factors affect SMK3 and the implementation and implementation of the SMK3 program. The method used in this study used a survey method through a questionnaire that was distributed to 35 respondents and then processed using SPSS software and presented in the form of a table. The results of the study stated that four variables that affect the SMK3 Implementation System, namely knowledge variables, work environment variables, K3 commitment variables, and compliance variables are statutory because the significance value of the four variables is < 0.05 also the results of the calculation analysis > table and the application of the Safety and Health Management System (SMK3) in the Rumdis Hubdam XVI / Pattimura-Ambon Rehab project, have been implemented very well.